2022
DOI: 10.1136/gutjnl-2021-326610
|View full text |Cite
|
Sign up to set email alerts
|

SK2 channels set a signalling hub bolstering CAF-triggered tumourigenic processes in pancreatic cancer

Abstract: ObjectiveIntercellular communication within pancreatic ductal adenocarcinoma (PDAC) dramatically contributes to metastatic processes. The underlying mechanisms are poorly understood, resulting in a lack of targeted therapy to counteract stromal-induced cancer cell aggressiveness. Here, we investigated whether ion channels, which remain understudied in cancer biology, contribute to intercellular communication in PDAC.DesignWe evaluated the effects of conditioned media from patient-derived cancer-associated fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Since P01 is highly active on SK2 channels and neither SK1 nor SK3 channels are expressed on U87 cells, we can suggest that SK2 channels are involved in the U87 cell tumorigenesis. This is in agreement with a recent paper demonstrating that SK2 channel, expressed in pancreatic ductal adenocarcinoma, increased invasiveness and metastasis formation, an effect that depends on cancer-associated fibroblasts (CAF) promoting SK2 phosphorylation through an integrin-epidermal growth factor receptor (EGFR)-AKT (Protein kinase B) axis (Rapetti-Mauss et al, 2022).…”
Section: Figuresupporting
confidence: 93%
“…Since P01 is highly active on SK2 channels and neither SK1 nor SK3 channels are expressed on U87 cells, we can suggest that SK2 channels are involved in the U87 cell tumorigenesis. This is in agreement with a recent paper demonstrating that SK2 channel, expressed in pancreatic ductal adenocarcinoma, increased invasiveness and metastasis formation, an effect that depends on cancer-associated fibroblasts (CAF) promoting SK2 phosphorylation through an integrin-epidermal growth factor receptor (EGFR)-AKT (Protein kinase B) axis (Rapetti-Mauss et al, 2022).…”
Section: Figuresupporting
confidence: 93%
“…Finally, LPA can promote ovarian cancer cell migration by activating an epidermal growth factor receptor (EGFR)-dependent pathway. Indeed, it was recently reported that SK2 activity promoted cell migration and invasion in pancreatic cancer cells by enhancing an integrin-EGFR-AKT (Protein kinase B) pathway [22,43].…”
Section: Plasma Membrane and Intracellular Sk2 Regulate Cell Migrationmentioning
confidence: 99%
“…SK2 channels were also identified in intracellular compartments, such as mitochondria, the endoplasmic reticulum (ER), or vesicles, and notably controlling cell death [17][18][19][20]. Although there is little information on SKCa channels in cancers, these channels participated in cell proliferation and cell migration [21][22][23]. Our laboratory has described the role of plasma membrane SK3 in breast, melanoma, prostate, and colon cancer cell migration in vitro and in breast cancer metastasis in vivo [14 (p. 20), 15,21,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fibroblast Activating Protein Inhibitor (FAPI) is a tumor-specific tracer on which we already have important clinical studies. This choice is because, in PDAC, more than 90% of the tumor volume consists of cancer-associated fibroblasts (CAFs) that are associated with the promotion of tumor growth, tissue invasion, metastasis development, immune escape, and resistance to therapy [142][143][144]. Considering the high expression of the FAP on the cell surfaces of CAFs and its limited expression in normal tissue, PET/CT imaging of CAFs with radiolabeled FAP inhibitors is an active field in nuclear medicine [137].…”
Section: Resectability After Nat/nacrtmentioning
confidence: 99%